2010
DOI: 10.1038/ejhg.2010.150
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of partial 21q monosomies with variable phenotypes

Abstract: Partial monosomy 21 was recently segregated into three regions associated with variable clinical severity. We describe 10 new patients, all examined by single nucleotide polymorphism (SNP) genotyping and G-banded karyotyping. Cohort A consisted of three patients seen in our medical genetics clinics with partial chromosome 21 monosomies. In two of these patients having terminal deletions (21q22.2-ter and 21q22.3-ter), the breakpoints differed by at least 812 Kb of sequence, containing seven RefSeq genes. A thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
1
9

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 9 publications
(8 reference statements)
8
79
1
9
Order By: Relevance
“…It was observed that proximal deletion of 21q is associated with mild or no cognitive impairment and problems with balance [9]. Deletion sizes of 4.86 Mb, 5.68 Mb and 16.4 Mb in three different patients were reported by Roberson et al [1] and 4.9 Mb in another patient by Valetto et al [4] compared to deletion size 9,151 Mb in our patient.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It was observed that proximal deletion of 21q is associated with mild or no cognitive impairment and problems with balance [9]. Deletion sizes of 4.86 Mb, 5.68 Mb and 16.4 Mb in three different patients were reported by Roberson et al [1] and 4.9 Mb in another patient by Valetto et al [4] compared to deletion size 9,151 Mb in our patient.…”
Section: Discussionmentioning
confidence: 77%
“…They suggested that the critical region of deletion lies within 21q22.1-q22.2. More sever phenotypes associated with 21q22 deletion were reported such as intrauterine growth retardation, microcephaly, seizures, corpus callosum abnormalities, eye anomalies, micrognathia, abnormal/dysplastic ears, intellectual disability [1,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic and molecular analysis of patients with partial monosomy 21 has been reported before (Chettouh et al, 1995;Roberson et al, 2011;Valero et al, 1999), but none, as far as we know, were associated to a chromosome pericentric inversion. The majority of these partial monosomies is de novo and reported on cytogenetic level, and only a few are submicroscopic deletions.…”
Section: Discussionmentioning
confidence: 99%
“…The proband also presents thick and everted vermillion of the upper lip. resulting in phenotypes including intellectual disability, brain dysgenesis, extensive dysmorphic features (microcephaly, short neck, epicanthic folds, flat nasal bridge, low set/malformed ears, highly arched palate, and transverse palmar crease), heart and/or renal defects (Migdalska et al, 2012;Roberson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%